2012
DOI: 10.1002/humu.22014
|View full text |Cite
|
Sign up to set email alerts
|

A frequent somatic mutation in CD274 3′-UTR leads to protein over-expression in gastric cancer by disrupting miR-570 binding

Abstract: Inhibitory costimulatory molecule CD274 expresses in various cancers and contributes to cancer immune evasion by inhibiting T cell activation and proliferation, yet the regulatory mechanisms for CD274 overexpression in cancers are poorly understood. In this study, we discovered a novel mechanism of CD274 expression regulated by miR-570. A guanine-to-cytosine mutation at the 3'-UTR of CD274 mRNA led to CD274 overexpression by disrupting the miR-570 binding. The mutations were widely observed in cancers by seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 13 publications
(18 reference statements)
1
62
0
2
Order By: Relevance
“…miRNAs are endogenous non-coding RNA of ~23 nucleotides, which inhibit protein translation by interacting with the 3′-untranslated regions (3′-UTRs) of the messenger RNAs (mRNAs) of target genes [17]. Although miRNAs have been increasingly described to be involved in the inhibition of B7/CD28 molecules [1824], further investigations are needed to fully understand whether they participate in TGF-β1-mediated regulation of B7/CD28 molecules in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are endogenous non-coding RNA of ~23 nucleotides, which inhibit protein translation by interacting with the 3′-untranslated regions (3′-UTRs) of the messenger RNAs (mRNAs) of target genes [17]. Although miRNAs have been increasingly described to be involved in the inhibition of B7/CD28 molecules [1824], further investigations are needed to fully understand whether they participate in TGF-β1-mediated regulation of B7/CD28 molecules in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently demonstrated that B7-H1 expression in cancer cells is regulated by miRNAs [16, 17]. To determine whether the HP-induced increase in B7-H1 expression in human gastric cancer cells occurs via miRNAs targeting B7-H1, we studied two candidate B7-H1 miRNAs (miR-152 and miR-200b) that were predicted byTargetScan and PicTar in AGS cells after HP infection.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, B7-H1 is an indicator of poor prognosis in patients with renal cell carcinoma [31], esophageal cancer [22], gastric carcinoma [7], breast cancer [32], ovarian cancer [33], bladder urothelial carcinoma [34], or pancreatic cancer [35]. It has been confirmed that the extent of B7-H1 expression in gastric cancer is significantly related to the clinicopathological features, including tumor size, depth of invasion, lymph node metastasis, and prognosis of patients [7, 17]. The results of our study demonstrated that B7-H1 expression in gastric cancer was associated with tumor malignancy; that is, the higher the expression of B7-H1, the lower the differentiation of the gastric cancer and the higher the TNM stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDCA7L interacts with c-Myc in bringing about cellular transformation in medulloblastoma [37]. Mutation of CD274 leading to its overexpression have been associated with gastric carcinoma [38]. Apart from these, mutations in ODZ1, TTN and EP300 are already reported in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%